1997
DOI: 10.1021/la960599+
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Precipitation in Reverse Micellar Systems

Abstract: A model of the precipitation process in reverse micelles has been developed to calculate the size of fine particles obtained therein. While the method shares several features of particle nucleation and growth common to precipitation in large systems, complexities arise in describing the processes of nucleation, due to the extremely small size of a micelle and of particle growth caused by fusion among the micelles. Occupancy of micelles by solubilized molecules is governed by Poisson statistics, implying most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 8 publications
0
55
0
Order By: Relevance
“…Bandyopadhyaya et al (Bandyopadhyaya et al, 1997) (Chew et al, 1990) have studied the effect of alkanes in the formation of AgBr particles in ionic W/O microemulsions (using AOT as surfactant), where the transmittance of the reactions were followed with time with UV-Vis and Stopped-Flow Spectrophotometry. They have found an increase on reaction rate with the chain lenght of the alkane.…”
Section: Reaction Kineticsmentioning
confidence: 99%
“…Bandyopadhyaya et al (Bandyopadhyaya et al, 1997) (Chew et al, 1990) have studied the effect of alkanes in the formation of AgBr particles in ionic W/O microemulsions (using AOT as surfactant), where the transmittance of the reactions were followed with time with UV-Vis and Stopped-Flow Spectrophotometry. They have found an increase on reaction rate with the chain lenght of the alkane.…”
Section: Reaction Kineticsmentioning
confidence: 99%
“…Although there is some difference in compositions of HAB from different sources, it is confirmed that they are mainly composed of dialkylbenzene and monoalkylbenzene with paraffinic side chains ranging from C 11 to C 22 , a small amount of other aromatic derivatives such as diphenylalkane and dialkyltetralin analyzed by Fourier transform infrared spectroscopy (FTIR) [5], gas chromatography and mass spectrometry (GC/MS) techniques [6][7][8]. It is believed that synthetic sulfonates are an important outlet for utilizing HAB byproducts with high additional value and the heavy alkylbenzene sulfonate (HABS) is evaluated as a starting material for preparing overbased sulfonate detergents [8][9][10].…”
Section: Introductionmentioning
confidence: 97%
“…With respect to the last aspect, these models (see overview in [28]) can be classified into two groups, namely stochastic models [29][30][31][32][33][34][35][36][37] which comprehend stochastic population balance equations, Monte-Carlo simulation models, and deterministic models [10,15,19,[38][39][40] where the latter comprise population balance models, moment models and simple analytical solutions. The main difference between models of the two groups lies in the complexity which is taken into account to achieve a solution at reasonable computational effort.…”
Section: Introductionmentioning
confidence: 99%